Corporate governance in banking and finance - Reddy, Y. R. K., 1949-; Raju, B. Yerram, 1941- (New Delhi : Tata McGraw-Hill Pub. Co., 2000)
Compilaton of articles presented at a conference with reference to India.
Includes bibliographical references
Keywords: Banks and banking -- India; Corporations -- India -- Finance; Financial institutions -- Government policy -- India